Problèmes des consignes dans les méthodes des Francais langue étrangère. Étude de cas de L'expression écrite dans la méthode studio 100 : - Nguyen, Thi Quynh Hoa (Universite de Can Tho, 2010)
The purpose of this research is to study types of "consigne" in " la méthode STUDO 100" through exercises of written expressions on students of English who study French as second foreign language in colledge of pedagogy of Can Tho